ETHNOBOTANI DALAM RITUAL PERNIKAHAN MASYARAKAT DESA SIDOMULYO KECAMATAN MEGALUH KABUPATEN JOMBANG JAWA TIMUR - Siti Latifah; Mucharommah Sartika Ami (Sekolah Tinggi Pariwisata Mataram, 2022)
Marriage is a sacred ritual to unite two people, in marriage each region has a variety of different and unique characteristics, such as the wedding in Sidomulyo village, Megaluh Jombang district, East Java, which has various rituals in it by utilizing the natural wealth of the surrounding plants. starting from the siraman ceremony, the widodareni ceremony and the side-by-side ceremony. For this reason, this research is intended to examine more deeply what ethnobotany is used in wedding rituals in this Sidomulyo village. In this study, researchers also used a qualitative method as a sample.